2007
DOI: 10.1074/jbc.m606610200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt2 Coordinates the Commitment of Mesoderm to Hematopoietic, Endothelial, and Cardiac Lineages in Embryoid Bodies

Abstract: Our recent gene expression profiling analyses demonstrated that Wnt2 is highly expressed in Flk1؉ cells, which serve as common progenitors of endothelial cells, blood cells, and mural cells. In this report, we characterize the role of Wnt2 in mesoderm development during embryonic stem (ES) cell differentiation by creating ES cell lines in which Wnt2 was deleted. Wnt2؊/؊ embryoid bodies (EBs) generated increased numbers of Flk1؉ cells and blast colony-forming cells compared with wild-type EBs, and had higher Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 41 publications
6
56
2
Order By: Relevance
“…This is further supported by other studies that report the differential WNT5a and WNT11 gene expression during embryonic development (37). In our study, we did not observe difference in the WNT2 expression between EBs of different sizes, which has been known to participate in mesoderm formation (38). Another important feature of our studies may be related to the size of the EBs and their influence on regulating the temporal expression of signaling molecules.…”
Section: Discussionsupporting
confidence: 91%
“…This is further supported by other studies that report the differential WNT5a and WNT11 gene expression during embryonic development (37). In our study, we did not observe difference in the WNT2 expression between EBs of different sizes, which has been known to participate in mesoderm formation (38). Another important feature of our studies may be related to the size of the EBs and their influence on regulating the temporal expression of signaling molecules.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it has previously been reported that Wnt2 plays an important role in the differentiation of embryonic stem cells [30]. However, the present results revealed little, if any, effect of Wnt2 on the cell proliferation and the level of the ALP activity and Runx2 and OC expression, all of which are key markers of osteoblast differentiation.…”
Section: Discussioncontrasting
confidence: 60%
“…67 It might be appropriate here to discuss the requirement of Wnt2b for cardiogenesis. 68 Wnt2b was initially found to be highly expressed in Flk1 ϩ progenitor cells 69 and subsequent generation of Wnt2b Ϫ/Ϫ ES cells indicated a requirement for Wnt2b for the cardiogenic but not for hematopoietic lineage. 68 More detailed analyses of these cells, however, indicated that the loss of Wnt2b is accompanied by an accelerated expression of Bry and Flk1.…”
Section: Cardiac Specification: Positive Influence Of Noncanonical Wnmentioning
confidence: 99%
“…68 Wnt2b was initially found to be highly expressed in Flk1 ϩ progenitor cells 69 and subsequent generation of Wnt2b Ϫ/Ϫ ES cells indicated a requirement for Wnt2b for the cardiogenic but not for hematopoietic lineage. 68 More detailed analyses of these cells, however, indicated that the loss of Wnt2b is accompanied by an accelerated expression of Bry and Flk1. This is an interesting observation given the positive role of Wnt/␤-catenin signaling for Bry expression, as discussed above.…”
Section: Cardiac Specification: Positive Influence Of Noncanonical Wnmentioning
confidence: 99%